2013
DOI: 10.1089/dia.2012.0202
|View full text |Cite
|
Sign up to set email alerts
|

Contact Heat-Evoked Potential Stimulation for the Evaluation of Small Nerve Fiber Function

Abstract: This study suggests that CHEPS is a novel, noninvasive technique able to detect impairment of small nerve fiber function from skin to cerebral cortex, providing an objective measure of C and Aδ nerve dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…In addition, CHEP N 2 –P 2 amplitudes at the ankle, more than at the wrist, showed acceptable diagnostic accuracy in differentiating between our controls and SFN patients, with reasonable sensitivity and specificity scores. Several studies have demonstrated increased CHEP latencies and reduced amplitudes in various forms of peripheral neuropathies that involve small nerve fibers . Our ROC findings (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, CHEP N 2 –P 2 amplitudes at the ankle, more than at the wrist, showed acceptable diagnostic accuracy in differentiating between our controls and SFN patients, with reasonable sensitivity and specificity scores. Several studies have demonstrated increased CHEP latencies and reduced amplitudes in various forms of peripheral neuropathies that involve small nerve fibers . Our ROC findings (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…They are thin, poorly myelinated, or unmyelinated, and therefore prone to destruction early in many pathological processes and often symptomatically debilitating. Indeed, the earliest changes appear to occur in the lower back, forearm, and thenar eminence as shown using Contact Heat Evoked Potential (CHEPS) (64), challenging the dogma that neuropathy is a distal to proximal disorder. Small nerves can be assessed objectively, and recognition of early dysfunction can allow intervention, treatment, and potentially cure.…”
Section: Resultsmentioning
confidence: 99%
“…An explanation for lower ESC values in the hands of T2DM females versus males found in the current study is not readily apparent, nor is the higher prevalence of moderate to severe sudomotor dysfunction in the hands versus feet. It should be noted that Parson et al [29] recently showed in a study of individuals with T2DM that the expected distal to proximal gradient usually seen in diabetic peripheral neuropathy was not observed in their evaluation of small fiber function measured using contact heat-evoked potential stimulation. The observations with regard to ESC of the hands shown in our study warrant additional investigation, with larger studies being required to completely address these findings.…”
Section: Discussionmentioning
confidence: 99%